Perspectives on Flood 1998 - Chowdhury, A. K. Azad; Imam, Syed Hasan; Sarker, Monaem, ed. (Dhaka : University Press Limited, 2000)
Environment Management
Includes index and bibliographical references
2001-01-08
Keywords: Floods